The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s0034-89102000000100007
|View full text |Cite
|
Sign up to set email alerts
|

Paridade e desenvolvimento ovariano de Anopheles albitarsis l.s. em área de agroecossistema irrigado

Abstract: OBJETIVO: Conhecer a paridade, o desenvolvimento ovariano e a razão de sobrevivência da espécie Anopheles albitarsis, visando a estimar o potencial de transmissão malárica. MÉTODOS: Duas populações de Anopheles albitarsis, denominadas A e B, foram capturadas na Fazenda Experimental do Instituto Agronômico de Campinas, situada no Município de Pariquera-Açu, Estado de São Paulo. As capturas foram feitas no período crepuscular vespertino das 17h às 20h, utilizando-se armadilha tipo Shannon. As dissecções foram fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
1
3
0
3
Order By: Relevance
“…may be signiÞcantly longer in the laboratory than in the Þeld (4.4 versus 2.4 d, P Ͻ 0.05, respectively). Given agreement between our results and previous reports for Þeld and laboratory conditions (Panday 1977, Charlwood and Alecrim 1989, Rubio-Palis et al 1994and Kakitani and Forattini 2000, there is a biologically signiÞcant difference between the estimates of gonotrophic cycle length based on laboratory or Þeld observations. We found that subsequent gonotrophic cycles were shorter than the Þrst under laboratory conditions, a characteristic suggested previously by Panday (1977).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…may be signiÞcantly longer in the laboratory than in the Þeld (4.4 versus 2.4 d, P Ͻ 0.05, respectively). Given agreement between our results and previous reports for Þeld and laboratory conditions (Panday 1977, Charlwood and Alecrim 1989, Rubio-Palis et al 1994and Kakitani and Forattini 2000, there is a biologically signiÞcant difference between the estimates of gonotrophic cycle length based on laboratory or Þeld observations. We found that subsequent gonotrophic cycles were shorter than the Þrst under laboratory conditions, a characteristic suggested previously by Panday (1977).…”
Section: Discussionsupporting
confidence: 88%
“…albitarsis s.l. under Þeld conditions (2.4 d) was similar to that described by Kakitani and Forattini (2000). Those authors used the method described by Davidson (Davidson 1954) and reported 1.990 d for An.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…En estudios epidemiológicos, la intensidad del contacto humano-vector en una población determinada se infiere por medio de la medición del índice de sangre humana, un indicador de su preferencia alimenticia 2-5 y por la medición del ciclo gonotrófico, un indicador de la frecuencia de alimentación, [6][7][8][9][10] puesto que los mosquitos requieren de al menos una alimentación sanguínea para producir cada lote de huevos. Si bien la información en estos indicadores es útil para evaluar la capacidad vectorial de diversas poblaciones de mosquitos, no permite identificar los factores que determinan la intensidad de contacto humanovector.…”
Section: Introductionunclassified
“…aegypti selvagens (50%), capturadas em Porto Rico, o que também aponta para a presença de discordância gonotrófica. Para Ae.scapularis, em condições de laboratório, TELLES DE DEUS eKAKITANI (2000)…”
unclassified